Analisis Nilai Sosial dalam Novel Siti Nurbaya Karya Marah Rusli - Trisnawati, Trisnawati (Jurnal Artikula, 2019)
This research aims to analyze the contents of Marah Rusli Siti Nurbaya novel. The authorin this study, wants to analyze the social values ​​that exist in the short story of Siti Nurbaya whichis divided into three studies in social values, namely social values ​​related to divinity, socialvalues ​​related to individuals, and social values ​​related to society. The method used in this studyis a qualitative method, a method that describes and analyzes each part of the contents in relationto social values ​​in the novel and describes social values ​​in the novel so that the writer candistinguish between the social values ​​of God, individuals, and society. The author chose this method because this method is suitable to be used as a way to analyze the social values ​​containedin the novel Siti Nurbaya, so that the analysis of the novel is easier and the author can present theresults of the analysis carefully, accurately and in detail and distinguish the social values​​contained in the novel.